Post-exercise effects of graduated compression garment use on skeletal muscle recovery and delayed onset muscle soreness: a systematic review - Araujo, Aline Machado (2018)
The study aimed to review the literature on the effects related to post-exercise of graduated compression garments (GCGs) use on muscle recovery and delayed onset muscle soreness. The search was performed in Pubmed/Medline, Bireme, Scielo, and Lilacs electronic databases using the following descriptors in English: "compression clothing", "physical exercise", "recovery", "physical activity", "compression stockings" and "delayed onset muscle soreness". The search resulted in 102 articles and after removing duplicates, applying exclusion criteria and checking the reference lists, nine studies fulfilled the criteria and were included in the review. Seven studies associated the use of GCGs with reduction of delayed muscle soreness and improvement in performance after the use of compression clothes. However, the methodological quality of the studies, using PEDro scale, presented an average of 5.1±0.9 points (out of a total of 11 points), classified as intermediate. In conclusion, although the positive effects of using CGCs on improving recovery and reduction of delayed muscle soreness after physical exercises are almost consensual, the insufficient methodological quality of the included studies requires careful consideration of the results.